Best evidence summary for the rational use of parenteral nutrition in hospitalized cancer patients - Liu, Zhengzheng; Liu, Beijia; Weng, Niannian; Gui, Qian; Liu, Di; Wu, Yuchi; Huang, Guiyu; Yang, Mingxue; Tang, Xiaoli (Frontiers in Nutrition, 2026)
ObjectiveTo systematically identify, review, and synthesize the best available evidence on the rational use of parenteral nutrition (PN) in hospitalized adult oncology patients, and to develop a practice-oriented framework encompassing decision-making, prescribing, review, compounding, administration, and monitoring, and quality management.MethodsPIPOST-based questions were developed to guide the review. Following the “5S” evidence-pyramid model, searches were performed in a top-down manner across system-level resources, guideline repositories, synthesis databases, and primary literature databases, including UpToDate, BMJ Best Practice, NICE, ESPEN, CSPEN, ASPEN, Chinese Certified Dietitian, Cochrane, JBI, PubMed, Embase, Web of Science, CINAHL, CNKI, Wanfang, and SinoMed. Eligible evidence types included clinical decision resources, clinical practice guidelines, systematic reviews and meta-analyses, expert consensus statements, and evidence summaries related to parenteral nutrition for hospitalized adult cancer patients. Study selection, quality appraisal, and data extraction were conducted independently by two trained reviewers, and any disagreements were resolved through discussion or adjudication by a third reviewer. Evidence items were regraded using the JBI pre-grading framework and synthesized thematically. The search covered all databases from their inception to 13 August 2025.ResultsA total of 2,248 records were retrieved. Eighteen documents met the inclusion criteria and were included: one system-level clinical decision resource, four clinical practice guidelines, nine expert consensus statements, and four systematic reviews. From these sources, 46 discrete evidence items were distilled and organized into five domains: individualized nutritional decision-making, PN prescribing and review, PN preparation and compounding, PN administration and monitoring, safety assessment and quality management.ConclusionParenteral nutrition for hospitalized cancer patients should be implemented within a multidisciplinary Nutrition Support Team (NST) framework and embedded within institutional quality management systems. Structured, individualized care plans should be developed based on the best available evidence. Given variability in institutional resources, staff competencies, and evidence across tumor subgroups, key quality indicators should be specified, and routine audits should be conducted during local implementation. The ultimate goal is to improve nutritional status, clinical outcomes, and the efficiency of healthcare resource utilization among hospitalized cancer patients.